Effect of Imidacloprid on the Testicular Activity and Endocrine Disruptive and Its Impact on Fertility in Male Rats - Mohammed S. A. Al-Awar (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study aims at finding out effect of imidacloprid (IM) on the testicular activity and endocrinedisruptive and its impact on fertility in male rats. Results. Administration of imidacloprid, orally (2 doses:45and 90 mg/kg b.w) to adult male rats for 4(D1), 8 (D2) or 12 (D3) weeks caused a disorganization ofthe spermatogenic cells, degeneration and congested of interstitial connective tissue, degeneration ofseminiferous tubule, reduction in number of cell layers per seminiferous tubules, number of seminiferoustubule sections, percentage of normal seminiferous tubules, seminiferous tubule diameter height of thegerminal epithelium, Infiltration of the immune-mononuclear cells, and a decrease in weight of the body,testes, epididymis, Vas deference, Seminal vesicle and prostate, this change was significant after 4 weeks oftreatment in high dose treated rats whereas it was significant after 8 weeks treatment in low dose treated rats,when compared to controls. Fertility index in female, Gestation index, weight of the litter born and numberpups to rats mated with IM treated (two doses) males in D2 or D3 was lower than controls whereas Gestationperiod, Fertility index of mal, viability index, Sex-ratio at birth did not significantly vary from controls.